PERKEBUNAN KELAPA RAKYAT DAN DAMPAK EKONOMISNYA TERHADAP PETANI KELAPA DI JAWA TIMUR PADA AWAL ABAD XX - Rucianawati, Rucianawati (Jurnal Sejarah dan Budaya, 2010)
Abstract: In the early twentieth century copra became one of the important export commodities in the Netherlands Indies. World demand was increasing along with the development of technology for its processing. Coconut products were not only for export but also for the interests of domestic industry. The increasing world demand for copra has consequences on the rise in commodity prices. But the rising standards of living of the coconut farmers were not comparable with the rising prices of coconut products in international markets. In the trade network, the middleman was the most widely reap the benefits. Coconut farmers are exploited by various bonding systems such as contracts, lien system, and retainer system.